Effect of capital structure and sales growth on firm value with profitability as mediation - Putri, I Gusti Agung Prabandari Tri; Rahyuda, Henny (International research journal of management, IT and social sciences, 2020)
This study aims to examine and analyze the effect of capital structure with the Debt to Equity Ratio proxy, sales growth with Sales Growth proxy and profitability with Return on Asset proxy on firm value with direct and indirect Price Book Value proxy using Return on Asset as a variable intervening. This study uses secondary data sourced from annual reports of 51 Consumer Good industrial companies listed on the Indonesia Stock Exchange for the period 2013-2018 as population. The sample selection is made by a purposive sampling technique that is the existence of certain criteria which are used as the basis for the selection of research samples. The results of the study are DER significant negative effect on ROA, SG significantly positive effect on ROA. DER does not affect PBV. SG has a significant positive effect on PBV. ROA can act as a mediator of the influence of DER, SG, and DPR on PBV.